THE PROBLEM OF TRANSFER SOME LETTER “MIN” IN TURKISH TRANSLATIONS OF THE QURAN - Arslan, Gyasettin (Yediveren Kitap, 2004)
The sacred books used the same language as the people. The Holy Quran gave the message to Arabic people with their own language. The three important elements of the Arabic language are: Noun, verb and letter. The letter of (min) is one of the these letters. In this article we will study the usage of the letter of (min) in the Quran and study how it was translated in to Turkish with it’s authentic meanings. As seen the recent Turkish translations of the Quran are observed to be bettter than those translated in the past. We have study nearly thirty Turkish translations of the Quran and we have want to showe some examples for this letter (min). Thus we desire to draw a conclusion.
TÜRKÇE KUR’AN MEALLERİNDE “MİN” HARFİNİN AKTARIM PROBLEMİ